Laboratory 3D printing system - V. Mironov, Anton; O. Mariyanac, Aleksandra; A. Mironova, Olga; K. Popov, Vladimir (International Journal of Engineering and Technology, 2018)
Present work describes the results of the development of the universal system, which capable to utilize varies 3D printing methodologies. The main goal of the study is to provide cheap, versatile and easy expandable equipment for multiple purpose research in the field of material science. 3D printing system was experimentally validated for fused deposition modeling, hydrogel, liquid dispensing and drop-on-demand printing, as well as 3D photopolymerisation by UV laser and/or LED light using different types of materials.Â Â